Evolusi Saluran Interaksi di Era Internet - Benedictus Arnold Simangunsong (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2011)
The development and advancement of technology affects how man interacts with others. The revolution of society interaction which was proposed by Straubhaar and LaRose, from pre-farming society to a farming society, into an industrial society, which was marked by the label of industrial revolution, to the information society, which is marked by the information revolution, shifted the way and man’s attitudes both in terms of economy and interaction. In the information society, the revolution also takes place in message delivery, where face-to-face was common at first, to textual and visual delivery, which is a change in the internet era.